Analysis of LINE1 Retrotransposons in Huntington’s Disease - Floreani, Lavinia; Ansaloni, Federico; Mangoni, Damiano; Agostoni, Elena; Sanges, Remo; Persichetti, Francesca; Gustincich, Stefano (Frontiers in Cellular Neuroscience, 2022)
Transposable elements (TEs) are mobile genetic elements that made up about half the human genome. Among them, the autonomous non-LTR retrotransposon long interspersed nuclear element-1 (L1) is the only currently active TE in mammals and covers about 17% of the mammalian genome. L1s exert their function as structural elements in the genome, as transcribed RNAs to influence chromatin structure and as retrotransposed elements to shape genomic variation in somatic cells. L1s activity has been shown altered in several diseases of the nervous system. Huntington disease (HD) is a dominantly inherited neurodegenerative disorder caused by an expansion of a CAG repeat in the HTT gene which leads to a gradual loss of neurons most prominently in the striatum and, to a lesser extent, in cortical brain regions. The length of the expanded CAG tract is related to age at disease onset, with longer repeats leading to earlier onset. Here we carried out bioinformatic analysis of public RNA-seq data of a panel of HD mice models showing that a decrease of L1 RNA expression recapitulates two hallmarks of the disease: it correlates to CAG repeat length and it occurs in the striatum, the site of neurodegeneration. Results were then experimentally validated in HttQ111 knock-in mice. The expression of L1-encoded proteins was independent from L1 RNA levels and differentially regulated in time and tissues. The pattern of expression L1 RNAs in human HD post-mortem brains showed similarity to mice models of the disease. This work suggests the need for further study of L1s in HD and adds support to the current hypothesis that dysregulation of TEs may be involved in neurodegenerative diseases.